GHAZALI'S VIEWS ON MORAL BEAUTY (Scientific journal of the Fergana State University, 2023)
The article analyzes the philosophical views of Abu Hamid Ghazali, including his works “Ey Farzand” and “Kimyoi Saodat” dedicated to the issues of man and his spiritual maturity.